The effect of different types of infographics on students' learning motivation in learning biology - Nur Alamsyah; Adnan Adnan; Muhiddin Palennari (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2025)
Students' success in achieving learning success is strongly influenced by learning motivation. This motivation can arouse students' interest, curiosity and enjoyment of learning materials. The main problem in learning biology related to motivation is using monotonous and less innovative media that makes students less motivated and the learning process less effective. Therefore, learning media is needed to increase students' motivation to learn. This study aimed to analyze the effect of static, animated and interactive infographics on the biology learning motivation of class XI SMA Negeri 3 Takalar students on the material of the circulatory system. The research design used was a true experiment with a pretest-posttest control group research design. The number of samples in this study was 144 students, consisting of four classes. The study's results with hypothesis testing using the ANCOVA test showed a significant effect of static, animated, and interactive infographics on students' biology learning motivation with a significance value of p <0.05. LSD's further test results show that the three types of infographics have the same effect and are different from handouts as a control. The results of this study produced visual, audio-visual and interactive-based learning media. This research makes a significant contribution to the field of education, especially in learning biology, by providing an understanding of the use of technology and learning media in the form of visualization of learning materials that affect student learning motivation.Abstrak. Keberhasilan peserta didik dalam mencapai keberhasilan belajar sangat dipengaruhi oleh motivasi belajar. Motivasi ini dapat membangkitkan minat, keingintahuan, dan rasa senang peserta didik terhadap materi pembelajaran. Permasalahan utama dalam pembelajaran biologi yang berkaitan dengan motivasi adalah penggunaan media yang monoton dan kurang inovatif, sehingga membuat peserta didik kurang termotivasi dan proses pembelajaran menjadi kurang efektif. Oleh karena itu, diperlukan media pembelajaran yang dapat meningkatkan motivasi belajar peserta didik. Penelitian ini bertujuan untuk menganalisis pengaruh media pembelajaran infografis statis, animasi, dan interaktif terhadap motivasi belajar biologi peserta didik kelas XI SMA Negeri 3 Takalar pada materi sistem peredaran darah. Desain penelitian yang digunakan adalah true experiment dengan desain penelitian pretest-posttest control group. Jumlah sampel pada penelitian ini sebanyak 144 peserta didik yang terdiri dari empat kelas. Hasil penelitian dengan uji hipotesis menggunakan uji ANCOVA menunjukkan adanya pengaruh yang signifikan infografis statis, animasi, dan interaktif terhadap motivasi belajar biologi peserta didik dengan nilai signifikansi p<0,05. Hasil uji lanjut LSD menunjukkan bahwa ketiga jenis infografis tersebut memiliki pengaruh yang sama dan berbeda dengan handout sebagai kontrol. Hasil penelitian ini menghasilkan media pembelajaran berbasis visual, audio-visual, dan interaktif. Penelitian ini memberikan kontribusi yang signifikan dalam bidang pendidikan khususnya dalam pembelajaran biologi, dengan memberikan pemahaman mengenai pemanfaatan teknologi dan media pembelajaran berupa visualisasi materi pembelajaran yang berpengaruh terhadap motivasi belajar peserta didik.